Virtual Museums: From Enthusiasm to Misunderstanding - Carmine Christian Ruocco (Umanistica Digitale)
Virtual museums, despite having generated significant interest over time, remain conceptually undefined and controversial, with no consensus on what the term precisely entails today. Initially, virtual museums referred to little more than a simple website. However, with advancements in computing capabilities and, above all, the emergence of Web 2.0, they have evolved into a complex entity encompassing a wide range of multimedia forms. This evolution has further highlighted the challenges cultural professionals face in understanding various technologies. The author—drawing on the substantial technological changes of the past two decades—aims to review both the history of the concept and its concrete applications. Additionally, the objective is to propose a new definition of the virtual museum, clarifying its utility for more effective dissemination and engagement.